A new Xymmer Santschi, 1914 (Formicidae: Amblyoponinae) species from the Congo Basin, with male and female descriptions of X. muticus (Santschi, 1914) - Hamer, Matthew T.; Gómez, Kiko; Jocque, Merlijn (Zootaxa, 2025)
The Amblyoponinae (Formicidae) ant genus Xymmer Santschi, 1914 currently comprises only two species, X. muticus (Santschi, 1914) and X. phungi Satria et al., 2016, from Africa and Southeast Asia respectively. Here we provide the first record of the genus from the Democratic Republic of the Congo (DRC), and describe the third species of the genus, the second for the Afrotropical region, X. paniscus sp. nov. Hamer, Gómez & Jocque 2024. Specimens originate from a rapid, multi-taxa biodiversity survey in the heart of Salonga National Park, in the Tshuapa province of the DRC. Further, we provide a worker redescription of X. muticus, and describe the alate gyne and male of the species. A dichotomous key to the known Xymmer species is also provided.